The CSR of Islamic banks and Halal businesses in the post Covid-19 pandemic era - Jaiyeoba, Haruna Babatunde; Azam, Md Siddique E (IIUM Press, 2023)
This paper discusses the CSR activities of Islamic banks and Halal companies in this era. As the world begins to transition from the Covid-19 pandemic, there is a need for Islamic banks and Halal businesses to retrospect into what has been learned during this crisis and to understand that stakeholders are now more concerned about how businesses operate and contribute to the betterment of the community than ever before. To avoid running the risk of losing customers and employees, Islamic banks and Halal companies must genuinely make large efforts to further their CSR initiatives by committing and promoting the greater good in society. The CSR sphere in post-Covid-19 must minimise, if not eliminate, the existential threat of the widening gap between the haves and have nots created by the Covid-19 outbreak. To this end, the researchers intend to identify and expose Islamic banks and Halal companies to various CSR activities that could help enhance their reputation, gain a competitive edge, achieve cost savings and operational efficiency, reinforce their credibility among Halal consumers and communities, manage their regulatory compliance and mitigate associated risks, and improve their long-term resilience and adaptability in this era. Specifically, the CSR activities covered in this study include commitment to Halal best practices, Zakat and charitable donations, Halal economic responsibility, legal responsibility, environmental responsibility, employee welfare, and responsible dealing with clients. Following the discussion of these CSR activities, the implications, with respect to the practice and theory, of this study are explicated, and recommendation and limitations of this study are offered.